Convention, Protest, or Violence? Estimating the Influence of Repertoires of Contention over Tactical Choice - Takeshi Wada; Yoojin Koo; Yoshiyuki Aoki (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
Why do people opt for different forms of collective action, like lobbying, marching, or rioting, to voice contentious claims? The patterns of these collective action forms, or “tactics” exhibit variations among groups, regions, and nations, evolving over time. Current explanations for such tactical patterns are unsatisfactory due to limited theoretical and empirical exploration of the concept of repertoires of contention. This paper presents a comprehensive theoretical model drawing on social practice and learning theories, centered around the notion of tactical familiarity. The central idea posits that people in diverse societies have learned distinct ways of doing politics, gaining varying familiarity and proficiency with different tactics, developed through three mechanisms: feedback, diffusion, and memory. These mechanisms contribute to the formation of notably distinct repertoires of contention. Based on this theoretical model, this study develops an empirical measure of tactical familiarity. The novel measure allows comparing the impact of tactical familiarity with other factors, like political regime characteristics. Previous research has not conducted such comparisons, as it often focuses on particular tactics, like protests or violence, without delving into the full array of potential tactical choices, including conventional-institutional ones. Using quantitative event analysis and a dataset of 10 Million International Dyadic Events, the paper examines 17,575 global political events from 2000 to 2004. Multilevel multinomial logistic regression highlights repertoires of contention’s significant influence on tactical choices, potentially outweighing political regime characteristics.